Wildlife Densities and Hunting by the Kenyah and Penan Communities in the Upper Baram Region, Sarawak - Nur Shahnaz, Binti Sahmat (2024)
Rapid forest conversion of tropical rainforests has caused detrimental effects on wildlife communities. Despite its importance as wildlife habitat, tropical forests play significant roles in the livelihood of many forest-dependent people. This study aims to explore the diversity and abundance of medium to large mammals in the Upper Baram region, Sarawak, Malaysian Borneo, where human and wildlife coexist. Using line-transect method, the study documented 17 species of medium to large mammals, including 13 endemic species of Borneo. Distance sampling method was used to estimate the densities of selected mammals’ species, including the Bearded pig (Sus barbatus), Long-tailed macaque (Macaca fascicularis) and Pig-tailed macaque (Macaca nemestrina). The study also assesses the hunting pattern and importance of wildlife in the livelihood of the Orang Ulu people, a group of indigenous ethnics in Sarawak living in the Upper Baram forest area. The study recorded 11 hunted animals, with Bearded pig (Sus barbatus) as the most hunted species. The results revealed an estimate of more than 5400 kg of wild meat were harvested over the study period. These findings are vital to provide information for future wildlife and forest conservation effort that considers the importance of the forest and its resources for the continuity of the local people traditional lifestyles in the region.